TMOD-08. ELUCIDATING EPIGENETIC MECHANISMS IN DIFFUSE INTRINSIC PONTINE GLIOMA HARBORING ACVR1 G328V AND H3.1 K27M. (23rd April 2019) - Mendez, Flor; Nunez, Felipe; Kadiyala, Padma; Ravindran, Ramya; Nunez, Fernando; Pawar, Sheeba; Williams, Jessica; Zorrilla-Veloz, Rocío; Swarnam, Umayal; Alcantara, Michelle; Parker, Ethan; Edwards, Marta; et al.
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a deadly pediatric brainstem tumor that originates in the pons. Mutations in Activin-A Receptor Type 1 (ACVR1), a bone morphogenetic protein (BMP) receptor, are highly recurrent and specific for DIPG. The ACVR1 mutations co-occur with the H3.1 K27M mutation. The K27M mutations are found in 80% of DIPG patients, occur on either HIST1H3B/C or H3F3A genes, and result in global hypo-methylation of H3K27me3. We used the Sleeping Beauty Transposase (SB) system to deliver plasmids encoding NRAS V12, short hair pin for TP53 (shp53), ACVR1-G328V with or without H3.1 K27M, into the brainstem of neonatal mice, to generate endogenous brainstem tumors. We also introduced the H3.1 K27M mutation to primary neurospheres harboring the ACVR1 G328V mutation. In vitro, tumor neurospheres harboring ACVR1-G328V exhibit elevated phopho-Smad1/5, transducer of the BMP pathway and expression of the H3.1 K27M mutation in these cells resulted in decreased levels of H3K27me3. To identify changes in the chromatin landscape induced by the H3.1 K27M mutation we performed ChIP-seq analysis for H3K27me3, H3k27ac, H3K27me1, and H3K4me3 on tumor neurospheres harboring ACVR1 G328V and neurospheres harboring ACVR1 G328V and H3.1 K27M. In summary, we used the SB transposase system to develop a mouse model that accurately represents the molecular characteristics of brainstem gliomas encoding ACVR1 G328V and H3.1 K27M mutations. We also developed an in vitro model using primary neurospheres from the SB model. In the future we aim to elucidate the epigenetic mechanisms by which ACVR1 and H3.1 K27M contribute to tumor development, and uncover novel therapeutic targets for DIPG. Work supported by NIH/NINDS; Leah's Happy Hearts Foundation and the ChadTough Foundation. FM is supported by an F31 Training Fellowship from NIH/NINDS.